2014
DOI: 10.1534/genetics.114.162800
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Local Regulatory Control of Escape from Imprinted X Chromosome Inactivation

Abstract: X chromosome inactivation (XCI) is an epigenetic process that almost completely inactivates one of two X chromosomes in somatic cells of mammalian females. A few genes are known to escape XCI and the mechanism for this escape remains unclear. Here, using mouse trophoblast stem (TS) cells, we address whether particular chromosomal interactions facilitate escape from imprinted XCI. We demonstrate that promoters of genes escaping XCI do not congregate to any particular region of the genome in TS cells. Further, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The Xi is a complex epigenomic landscape that includes genes capable of escaping XCI (Carrel and Willard, 2005;Li and Carrel, 2008;Yang et al, 2010;Calabrese et al, 2012;Pinter et al, 2012;Mugford et al, 2014). Allele-specific ChIP-seq of mouse trophoblast stem cells (TSC) previously showed that the majority of CTCF binding sites on the imprinted paternal Xi is shared with the active maternal Xa (Calabrese et al, 2012), and that no specific structural features were discernible for genes that escape XCI (Mugford et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Xi is a complex epigenomic landscape that includes genes capable of escaping XCI (Carrel and Willard, 2005;Li and Carrel, 2008;Yang et al, 2010;Calabrese et al, 2012;Pinter et al, 2012;Mugford et al, 2014). Allele-specific ChIP-seq of mouse trophoblast stem cells (TSC) previously showed that the majority of CTCF binding sites on the imprinted paternal Xi is shared with the active maternal Xa (Calabrese et al, 2012), and that no specific structural features were discernible for genes that escape XCI (Mugford et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Allele-specific ChIP-seq of mouse trophoblast stem cells (TSC) previously showed that the majority of CTCF binding sites on the imprinted paternal Xi is shared with the active maternal Xa (Calabrese et al, 2012), and that no specific structural features were discernible for genes that escape XCI (Mugford et al, 2014). Here we carried out allele-specific ChIP-seq (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, because the Xp is silenced, at least a functional maternal Ogt allele seems required in extra-embryonic tissues for proper preimplantation development. Surprisingly though, other studies have shown that Ogt does not systematically undergo normal iXCI in extra-embryonic tissues and have therefore defined Ogt as an iXCI-escaping gene in mouse trophoblastic stem cells [2831]. Thus, female placentas sometimes have higher levels of OGT and O- GlcNAcylated proteins than male placentas [32**].…”
Section: Dosage Of Ogt Is Regulated By Imprinted X-inactivationmentioning
confidence: 99%
“…Surprising though, more recent studies have shown that Ogt expression does not undergo normal iXCI in extraembryonic tissues. Indeed, a number of recent studies have identified Ogt as an iXCI-escaping gene in mouse trophoblast stem cells [51,52,53,54], suggesting that Ogt is never subjected to iXCI in extraembryonic tissues. Accordingly, biallelic expression of Ogt is detected in female mouse trophobast stem cells [51,53].…”
Section: Ogt Dosage In Extraembryonic Tissuesmentioning
confidence: 99%